Lombok Women: Dynamics, Transformation, and Socio-Economic Realities in the Family - Fatanah, Ahmad; Rasyidi, Abdul Haris (International Journal of Humanities, Education, and Social Sciences, 2024)
This article explores empirical insights into the role of women in Lombok society. The increasing responsibility of meeting family needs is examined through various analyses, notably sociological analysis. In many cases, Lombok women balance dual roles: as homemakers and as contributors to the family's everyday needs. This research employs a qualitative descriptive methodology with a phenomenological approach to comprehend the nuanced experiences and meanings attached to specific situations. Participants’ insights provide invaluable perspectives, facilitating a deeper exploration of the subjects under study. Data analysis utilizes sociological frameworks to elucidate the evolving social status of women in Lombok societies. The findings illustrate a dynamic socio-economic transformation among Lombok women, reflecting the growing significance of their contributions to family welfare. This transformation is driven by heightened daily living expenses, prompting a shift from traditional homemaker roles to becoming pivotal economic pillars within their families. Moreover, instances where wives possess higher educational attainment than their husbands underscore significant shifts in life dynamics and socio-economic structures.